The Prospects of Village Owned Enterprises Development in Igirisa Village, Paguyaman District Boalemo Regency - Roni Saidi; Ikram Muhammad; Fibriyanti S. Lakoro (Journal of Economic, Business, and Administration (JEBA), 2021)
The objectives of this research are (1) to find out the prospect of Village Owned Enterprises development (BUMDes) in Girisa Village, Paguyaman District, Boalemo Regency. (2) To determine the supporting and inhibiting factors of Village Owned Enterprises development (BUMDes) in Girisa Village, Paguyaman District, Boalemo Regency. (3) To find out the efforts made to overcome obstacles of Village Owned Enterprises development (BUMDes) in Girisa Village, Paguyaman District, Boalemo Regency.The research method used descriptive research with a qualitative approach. The data analysis technique used SWOT analysis. SWOT analysis is used to analyze prospects of Village Owned Enterprises development in Girisa Village, Paguyaman District, Boalemo Regency.The research results showed that (1) The prospect of Village Owned Enterprises development (BUMDes) in Girisa Village, Paguyaman District, Boalemo Regency which is considered not running optimally because gradually in the short-, medium- and long-term prospects have not been fulfilled. (2) The supporting factor for good cooperation between the Village Government and the high interest and interest of the community, while the inhibiting factor is the lack of BUMDes budget. Lack of competent BUMDes managers. The existence of a similar business where the presence of other parties from outside makes a business. Lack of promotion of BUMDes to the community and managers who do not have an entrepreneurial spirit. (3) Efforts made to overcome obstacles have minimal planning both short term and long term. There needs to be organizing so that a good organization can help BUMDes Bangkit Bersama be able to run well. Have good controlling (supervision). And have actuating (implementation), which is able to run well